Development of a Game-based Shot Put Motion Task for Junior Hight School Student - Komang , Agus Ariyana; Made , Agus Wijaya; Komang, Sukarata Adnyana (Universitas Pendidikan Ganesha, 2024)
PJOK learning motion tasks encourage students to learn to move and learn through movement in fun situations. The absence of game-based shot put material movement assignments for junior high school students prompted this development research to be carried out. Using the ADDIE model, this article focuses on discussing two stages, namely the design stage and the development stage. Game-based shot put material motion tasks are designed at easy, medium and hard difficulty levels. The research instrument consists of validation sheets from content experts and PJOK practitioners. Data analysis was carried out descriptively quantitative-qualitatively. The results of the research showed that the PJOK content expert's validation score reached 71, and the PJOK practitioner's score reached 72 from a maximum score of 75. Based on the results of the research and discussion, it was concluded that the game-based shot put material movement assignment for junior high school students was included in the very good category and met the criteria in accordance with curriculum, ensuring adequacy of movement, the presence of internalized character elements and ensuring the security and safety of students. It is recommended that PJOK SMP teachers can implement game-based shot put material motion tasks for SMP students.